2019
DOI: 10.1136/openhrt-2018-000866
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of walking fitness in patients with heart failure attending cardiac rehabilitation

Abstract: IntroductionPatients with heart failure (HF) attending cardiac rehabilitation (CR) benefit in terms of improved quality of life, physical fitness and reduced hospital admissions. Too few patients with HF attend CR and little data exist on the characteristics of those who do especially in respect of physical fitness. This study evaluates the extent by which clinical and demographic factors determine walking fitness in patients with a primary diagnosis of HF.MethodsClinical data from the British Heart Foundation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…It should however be borne in mind that HF has a progressive development (25) and that with age, the predicted walking distance and work capacity "normally" decreases (75,99). In line with study II, earlier studies have shown none or poor improvement by an exercise programme in HF patients (100,101).…”
Section: Exercise Trainingsupporting
confidence: 52%
“…It should however be borne in mind that HF has a progressive development (25) and that with age, the predicted walking distance and work capacity "normally" decreases (75,99). In line with study II, earlier studies have shown none or poor improvement by an exercise programme in HF patients (100,101).…”
Section: Exercise Trainingsupporting
confidence: 52%
“…On the other hand, this would make it possible to analyze the training effect with less confounders. Doherty et al [30] showed that patients with HF and comorbidities, walked 42 m shorter than patients with less comorbidity. Among the inclusion criteria were being in NYHA class II or III.…”
Section: Discussionmentioning
confidence: 99%
“…23 However, there is limited research examining clinical outcomes in adults with cardiorespiratory disease using national CR and PR audit data. 24 Furthermore, PR and CR programmes may view the presence of comorbidity differently, which may result in an enrolment and completion bias between those with cardiorespiratory disease or single cardiac/ pulmonary disease. Understanding this further may provide insight into how these patients travel through the UK healthcare system and the approach of PR and CR services, including the collection of appropriate outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…The UK's National Health Service (NHS) supports the delivery of one exercise rehabilitation programme for adults presenting with breathlessness [ 22 ], and there is support for individualised multi-morbid exercise rehabilitation [ 23 ]. However, there is limited research examining clinical outcomes in adults with cardiorespiratory disease using national CR and PR audit data [ 24 ]. Furthermore, PR and CR programmes may view the presence of comorbidity differently, which may result in an enrolment and completion bias between those with cardiorespiratory disease or single cardiac/ pulmonary disease.…”
Section: Introductionmentioning
confidence: 99%